Acid and alkali resistant anti-aging spinning yarn and preparation method thereof
By combining premodified nanomontmorillonite with phosphosilicon flame retardant additives and functionalized polyamides to form a crosslinked network structure, the problem of spinning yarns being susceptible to erosion in an acid-base environment is solved, the acid-base resistance and anti-aging properties of spinning yarns are significantly improved, the stability and service life of textiles are enhanced, and the antibacterial and flame-retardant properties are improved, ensuring the safety of human health.
Patent Information
- Application Number
- CN202411928209.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-01
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing spinning yarns are susceptible to erosion in acid-base environments, resulting in decreased strength and damaged quality, and are difficult to resist aging caused by factors such as light, temperature changes and humidity, affecting the service life of textiles and human health.
Modified nanomontmorillonite and 4-(dimethylamino)salicyaldehyde reaction are prepared by reacting premodified nanomontmorillonite and combined with phosphosilicon flame retardant additives and functionalized polyamides to form a crosslinking network structure to improve the acid and alkali resistance and anti-aging properties of the spinning yarn.
It significantly improves the acid and alkali resistance of spinning yarns, reduces the mass loss rate in the acid and alkali environment, enhances the stability and service life of textiles, and improves the antibacterial and flame retardant properties, ensuring the safety of human health.
Smart Images

Figure BDA0005209725990000121 
Figure BDA0005209725990000131
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of spinning yarns, in particular to an acid-base resistant and anti-aging spinning yarn and a preparation method thereof. Background Art
[0002] Spun yarn is the basic material of textiles. In daily use, textiles are exposed to various environmental conditions, such as light, temperature changes, humidity, and contact with chemicals, which may cause the aging of the yarn. As the yarn ages, its color may fade, its strength may decrease, and it may even break. This not only affects the aesthetics of the textile, but also its function. In an acid-base environment, the yarn is easily corroded by acids and alkalis, resulting in a decrease in the strength of the textile, damage to its quality, and even possible thread breakage. Especially in the chemical, pharmaceutical, and environmental protection industries, textiles are often exposed to acid and alkali substances, which will cause the performance of the textiles to decline, and they cannot be used normally, and may even cause safety accidents. The pH value of textiles has a direct impact on human skin. If the pH value of textiles is too high or too low, it will destroy the balance and resistance of the skin, causing skin allergies or inducing infections.
[0003] Improving the acid, alkali and aging resistance of yarns can enable them to better resist the erosion of these external factors, enhance the stability and service life of textiles, and is of great significance for meeting the needs of specific industries and protecting human health. Summary of the invention
[0004] The purpose of the present invention is to provide an acid-base resistant and anti-aging spinning yarn and a preparation method thereof, so as to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] A kind of acid and alkali resistant anti-aging spinning yarn, the acid and alkali resistant anti-aging spinning yarn is prepared by reacting pre-modified nano-montmorillonite and 4-(dimethylamino) salicylaldehyde to obtain modified nano-montmorillonite; polycondensing 3-chloropropylmethyldiethoxysilane and phosphorus-containing diethoxysilane to obtain phosphorus silicon flame retardant additive; polycondensing polyamic acid solution, N 4 ,N 4 -dimethyl-1,2,4-phenyltriamine is reacted to obtain functionalized polyamide; functionalized polyamide, modified nano-montmorillonite and phosphorus silicon flame retardant additive are prepared into spinning solution, and polyamide fiber is obtained by electrostatic spinning; polyamide fiber is spun in a spinning machine to obtain acid-base resistant and anti-aging spinning yarn;
[0007] The pre-modified nano-montmorillonite is prepared by reacting nano-montmorillonite and 4-anilinotriethoxysilane;
[0008] The phosphorus-containing diethoxysilane is prepared by reacting 3-(diethoxymethylsilyl)propylamine and diphenylphosphine;
[0009] The polyamic acid solution is prepared by polymerizing 3,3',4,4'-biphenyltetracarboxylic dianhydride, 4,4'-(hexafluoroisopropylene) diphthalic anhydride and 1,6-hexamethylenediamine.
[0010] A method for preparing an acid- and alkali-resistant anti-aging spun yarn, the method comprising the following preparation steps:
[0011] (1) Pre-modified nano-montmorillonite and toluene are mixed uniformly in a mass ratio of 1:(52-54), ultrasonically dispersed for 20-30 min, 4-(dimethylamino) salicylaldehyde in an amount of 2.8-3.2 times the mass of the pre-modified nano-montmorillonite is added, stirred at 60-66°C and 200-300 r / min for 3-4 h, filtered, washed with toluene 3-5 times, and dried at 68-70°C under vacuum conditions for 8-10 h to obtain modified nano-montmorillonite;
[0012] (2) 3-chloropropylmethyldiethoxysilane and phosphorus-containing diethoxysilane are added to a reaction kettle in a molar ratio of 1:(1.1-1.3), deionized water of 1.2-1.4 times the mass of 3-chloropropylmethyldiethoxysilane and lithium hydroxide of 0.02-0.03 times the mass of 3-chloropropylmethyldiethoxysilane are added, and the temperature is raised to 80-82°C at a rate of 3°C / min under stirring conditions of 100-200 r / min, and the stirring reaction is continued for 28-32 minutes, and the mixture is washed with an equal volume of deionized water and toluene, and the mixture is allowed to stand for stratification, and the aqueous phase is removed, and the washing is repeated 4-6 times, and the organic phase is placed in a drying oven, and dried at 58-62°C for 8-10 hours under vacuum conditions to obtain a phosphorus silicon flame retardant additive;
[0013] (3) adding 3,3',4,4'-biphenyltetracarboxylic acid dianhydride and 4,4'-(hexafluoroisopropylene) diphthalic anhydride in a molar ratio of 1:(0.4-0.6) to N,N-dimethylformamide which is 7-8 times the mass of 3,3',4,4'-biphenyltetracarboxylic acid dianhydride, and mixing them uniformly to prepare a dianhydride reaction liquid; adding 3,3',4,4'-biphenyltetracarboxylic acid dianhydride, 4,4'-(hexafluoroisopropylene) diphthalic anhydride, and the mixture is stirred for 2 h. 1 times the molar amount of 1,6-hexanediamine and N,N-dimethylformamide are mixed uniformly in a mass ratio of 1:(6-8), stirred at 10-30°C and 200-300r / min for 10-12min under nitrogen protection, and the dianhydride reaction liquid is added, and stirred at 10-30°C and 300-500r / min for 18-20h under nitrogen atmosphere to obtain a polyamic acid solution; the polyamic acid solution and N 4 ,N 4-Dimethyl-1,2,4-phenyltriamine and hydrochloric acid aqueous solution are mixed uniformly in a mass ratio of 1:(0.22-0.24):(0.06-0.08), stirred at 80-90°C and 60-80r / min for 7-8h, and dried at 76-78°C under vacuum conditions for 9-11h to obtain functionalized polyamide;
[0014] (4) Functionalized polyamide, modified nano-montmorillonite, phosphorus silicon flame retardant additive and N,N-dimethylformamide are mixed uniformly, and stirred at 10-30°C and 100-120 r / min for 18-20 min to prepare a spinning solution; the spinning solution is loaded into a micro pump, and an ice plate covered with aluminum foil is used as a receiving device, and electrospinning is performed in an electrospinning device to obtain spun fibers; the spun fibers are allowed to stand at 58-60°C for 2-2.2 h, and dried at 70-72°C under vacuum conditions for 7-9 h to obtain polyamide fibers; the polyamide fibers are spun in a spinning machine to obtain acid- and alkali-resistant and anti-aging spinning yarns.
[0015] As an optimization, the preparation method of the pre-modified nano-montmorillonite in step (1) is: nano-montmorillonite and anhydrous ethanol are mixed evenly in a mass ratio of 1:(57-63), silane hydrolyzate is added in an amount of 6-7 times the mass of the nano-montmorillonite, the reaction is carried out at 56-58°C, 200-300 r / min, and the reaction is stirred for 1-1.2 h, filtered, washed with anhydrous ethanol for 3-5 times, and dried at 56-58°C under vacuum conditions for 8-10 h to obtain the pre-modified nano-montmorillonite.
[0016] As an optimization, the preparation method of the silane hydrolyzate is: 4-anilinotriethoxysilane and deionized water are mixed evenly in a mass ratio of 1:(18-20), the pH is adjusted to 5.8-6.2 with an oxalic acid aqueous solution, and stirred at 200-300 r / min for 15-25 minutes at room temperature to prepare a silane hydrolyzate.
[0017] As an optimization, the mass fraction of the oxalic acid aqueous solution is 10% to 12%.
[0018] As an optimization, the preparation method of the phosphorus-containing diethoxysilane in step (2) is: 3-(diethoxymethylsilyl)propylamine and diphenylphosphine are added in a molar ratio of 1:1 to acetonitrile with a mass of 10 to 12 times that of 3-(diethoxymethylsilyl)propylamine, and cuprous iodide with a mass of 0.03 to 0.05 times that of 3-(diethoxymethylsilyl)propylamine is added, and the reaction is stirred at 55 to 57° C. and 200 to 300 r / min for 4 to 5 hours, and dried at 69 to 71° C. under vacuum conditions for 8 to 10 hours to obtain the phosphorus-containing diethoxysilane.
[0019] As an optimization, the molar concentration of the hydrochloric acid aqueous solution in step (3) is 4 mol / L.
[0020] As an optimization, the mass ratio of the functionalized polyamide, modified nano-montmorillonite, phosphorus silicon flame retardant additive, and N,N-dimethylformamide in step (4) is 1:(0.04-0.06):(0.06-0.08):(6-7).
[0021] As an optimization, the process parameters of the electrospinning in step (4) are as follows: adjusting the receiving distance to 16-18 cm, the voltage during spinning to 23-25 kV, the propulsion rate to 0.6-0.7 mL / h, the ambient temperature to 20-30° C., and the spinning humidity to 50%-60%.
[0022] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0023] When preparing the acid-base resistant and anti-aging spinning yarn, the present invention comprises the following steps: reacting nano-montmorillonite and 4-anilinotriethoxysilane to obtain pre-modified nano-montmorillonite; reacting pre-modified nano-montmorillonite and 4-(dimethylamino) salicylaldehyde to obtain modified nano-montmorillonite; reacting 3-(diethoxymethylsilyl)propylamine and diphenylphosphine to obtain phosphorus-containing diethoxysilane; polycondensing 3-chloropropylmethyldiethoxysilane and phosphorus-containing diethoxysilane to obtain phosphorus silicon flame retardant additive; polymerizing 3,3',4,4'-biphenyltetracarboxylic anhydride, 4,4'-(hexafluoroisopropylene) diphthalic anhydride and 1,6-hexanediamine to obtain a polyamic acid solution; and reacting the polyamic acid solution, N 4 ,N 4 -Dimethyl-1,2,4-phenyltriamine is reacted to obtain functionalized polyamide; the functionalized polyamide, modified nano-montmorillonite and phosphorus silicon flame retardant additive are prepared into spinning solution, and polyamide fiber is obtained by electrospinning; the polyamide fiber is spun in a spinning machine to obtain acid-base resistant and anti-aging spinning yarn.
[0024] Firstly, nano-montmorillonite and 4-anilinotriethoxysilane are reacted to obtain pre-modified nano-montmorillonite, and aniline is introduced into the pre-modified nano-montmorillonite; the aniline on the pre-modified nano-montmorillonite is reacted with the aldehyde group on 4-(dimethylamino) salicylaldehyde to generate a salicylaldehyde aniline Schiff base structure, and a tertiary amine structure is introduced to obtain modified nano-montmorillonite; there is a hydroxyl group at the ortho position of the C=N double bond in the salicylaldehyde aniline Schiff base structure, and under ultraviolet light irradiation, the hydrogen atom on the hydroxyl group in the molecular structure is transferred from the oxygen atom to the ortho position of the nitrogen atom, and proton transfer occurs within the molecule, and the configuration of the salicylaldehyde aniline Schiff base structure is converted from an enol form to a keto form, and the generated keto form structure is unstable and is converted into an ene form again under light or heating. Alcohol structure, thereby dissipating the ultraviolet light absorption, giving the acid-resistant and alkali-resistant anti-aging spinning yarn excellent anti-aging properties; the tertiary amine structure introduced on the modified nano-montmorillonite can react with the chlorine atoms on the phosphorus silicon flame retardant additive to generate quaternary ammonium salts, forming a cross-linked network structure, and improving the mechanical properties of the acid-resistant and alkali-resistant anti-aging spinning yarn; the generated quaternary ammonium salt structure can improve the antibacterial properties of the acid-resistant and alkali-resistant anti-aging spinning yarn; nano-montmorillonite is a two-dimensional inorganic nanomaterial, and the dispersibility of nano-montmorillonite in the resin is improved through surface modification, so that the nano-montmorillonite is evenly dispersed in the resin to form a physical barrier, making the diffusion process of water molecules more tortuous and slow, reducing the penetration of gases and liquids, and improving the acid and alkali resistance of the acid-resistant and alkali-resistant anti-aging spinning yarn.
[0025] Secondly, the amino group on 3-(diethoxymethylsilyl)propylamine reacts with the PH bond on diphenylphosphine to obtain phosphorus-containing diethoxysilane; 3-chloropropylmethyldiethoxysilane and phosphorus-containing diethoxysilane are polycondensed to obtain a phosphorus silicon flame retardant additive, Si-O-Si bonds are generated on the main chain of the phosphorus silicon flame retardant additive, and phosphorus and chlorine atoms are introduced on the side chain; the bond energy of the Si-O bond is greater than that of the CC bond, and a dense barrier carbon layer is formed during the combustion process. This carbon layer can effectively prevent heat conduction and oxygen diffusion, thereby improving the flame retardant properties of the acid and alkali resistant and anti-aging spinning yarn, and the introduction of phosphorus further improves the flame retardancy; the chlorine atoms introduced on the side chain of the phosphorus silicon flame retardant additive can react with the tertiary amine structure introduced on the modified nano-montmorillonite and the functionalized polyamide to generate a quaternary ammonium salt structure, forming a cross-linked network, inhibiting the relative slip between molecular chains, and improving the mechanical properties of the acid and alkali resistant and anti-aging spinning yarn.
[0026] Finally, 3,3',4,4'-biphenyltetracarboxylic anhydride, 4,4'-(hexafluoroisopropylene) diphthalic anhydride and 1,6-hexamethylenediamine were polymerized to obtain a polyamic acid solution; the carboxyl groups on the side chains of the polyamic acid molecules in the polyamic acid solution were reacted with N 4 ,N 4-O-phenylenediamine reacts with dimethyl-1,2,4-benzenetriamine to generate a benzimidazole structure to obtain a functionalized polyamide, and at the same time, a tertiary amine structure and a fluorine atom are introduced into the side chain of the functionalized polyamide molecule; the generated benzimidazole structure can improve the antibacterial properties of the acid-base resistant and anti-aging spinning yarn; the tertiary amine structure introduced into the side chain of the functionalized polyamide molecule can react with the chlorine atom introduced into the side chain of the phosphorus silicon flame retardant additive to generate a quaternary ammonium salt structure, form a cross-linked network, inhibit the relative slip between the molecular chains, and improve the mechanical properties of the acid-base resistant and anti-aging spinning yarn; the generated quaternary ammonium salt structure has excellent antibacterial properties and can improve the antibacterial properties of the acid-base resistant and anti-aging spinning yarn; the electronegativity of the fluorine atom introduced into the side chain of the functionalized polyamide molecule is very large, which enables the fluorine atom to strongly attract electrons to form a stable CF bond. Due to the high bond energy of the CF bond and the low surface tension of the fluorocarbon chain, the acid-base resistant and anti-aging spinning yarn has hydrophobicity and oleophobicity, giving the acid-base resistant and anti-aging spinning yarn excellent acid-base resistance. DETAILED DESCRIPTION
[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0028] Embodiment 1:
[0029] A method for preparing an acid- and alkali-resistant anti-aging spun yarn, the method comprising the following preparation steps:
[0030] (1) 4-anilinotriethoxysilane and deionized water were mixed at a mass ratio of 1:18, the pH was adjusted to 5.8 with a 10% oxalic acid aqueous solution, and stirred at room temperature at 200 r / min for 25 min to prepare a silane hydrolyzate; nano-montmorillonite and anhydrous ethanol were mixed at a mass ratio of 1:57, and silane hydrolyzate with a mass of 6 times that of nano-montmorillonite was added, and the mixture was stirred at 56°C and 200 r / min for 1.2 h, filtered, and used The pre-modified nano-montmorillonite was prepared by washing with anhydrous ethanol for 3 times and drying at 56°C for 10 hours under vacuum conditions. The pre-modified nano-montmorillonite and toluene were mixed evenly at a mass ratio of 1:52, ultrasonically dispersed for 20 minutes, and 4-(dimethylamino) salicylaldehyde, which was 2.8 times the mass of the pre-modified nano-montmorillonite, was added, stirred at 60°C and 200 r / min for 4 hours, filtered, washed with toluene for 3 times, and dried at 68°C for 10 hours under vacuum conditions to obtain modified nano-montmorillonite.
[0031] (2) 3-(diethoxymethylsilyl)propylamine and diphenylphosphine were added in a molar ratio of 1:1 to acetonitrile with a mass of 10 times that of 3-(diethoxymethylsilyl)propylamine, and cuprous iodide with a mass of 0.03 times that of 3-(diethoxymethylsilyl)propylamine was added, and the mixture was stirred at 55°C and 200 r / min for 5 h, and dried at 69°C for 10 h under vacuum conditions to obtain phosphorus-containing diethoxysilane; 3-chloropropylmethyldiethoxysilane and phosphorus-containing diethoxysilane were added in a molar ratio of 1:1.1 to the reaction mixture. In the reaction kettle, add deionized water of 1.2 times the mass of 3-chloropropylmethyldiethoxysilane and lithium hydroxide of 0.02 times the mass of 3-chloropropylmethyldiethoxysilane, and heat to 80°C at a rate of 3°C / min under stirring at 100 r / min, continue stirring and reacting for 32 minutes, wash with a mixture of equal volumes of deionized water and toluene, let stand to separate, remove the water phase, repeat washing 4 times, take the organic phase and place it in a drying oven, dry it at 58°C for 10 hours under vacuum conditions, and obtain a phosphorus silicon flame retardant additive;
[0032] (3) adding 3,3',4,4'-biphenyltetracarboxylic acid dianhydride and 4,4'-(hexafluoroisopropylene) diphthalic anhydride in a molar ratio of 1:0.4 to N,N-dimethylformamide (7 times the mass of 3,3',4,4'-biphenyltetracarboxylic acid dianhydride) and mixing them evenly to prepare a dianhydride reaction liquid; mixing 3,3',4,4'-biphenyltetracarboxylic acid dianhydride and 1,6-hexanediamine (1 times the total molar amount of 4,4'-(hexafluoroisopropylene) diphthalic anhydride) and N,N-dimethylformamide in a mass ratio of 1:6 evenly, stirring at 10°C and 200 r / min for 12 minutes under nitrogen protection, adding the dianhydride reaction liquid, stirring at 10°C and 300 r / min for 20 hours under nitrogen atmosphere to prepare a polyamic acid solution; mixing the polyamic acid solution and N 4 ,N 4 -Dimethyl-1,2,4-phenyltriamine and a hydrochloric acid aqueous solution with a molar concentration of 4 mol / L were mixed uniformly in a mass ratio of 1:0.22:0.06, stirred at 80°C and 60 r / min for 8 hours, and dried at 76°C for 11 hours under vacuum conditions to obtain a functionalized polyamide;
[0033] (4) Functionalized polyamide, modified nano-montmorillonite, phosphorus silicon flame retardant additive, and N,N-dimethylformamide were mixed uniformly in a mass ratio of 1:0.04:0.06:6, and stirred at 10°C and 100 r / min for 20 min to prepare a spinning solution; the spinning solution was loaded into a micro pump, and an aluminum foil covered on an ice plate was used as a receiving device, and the receiving distance was adjusted to 16 cm. During the spinning process, the voltage was 23 kV, the propulsion rate was 0.6 mL / h, the ambient temperature was 20°C, and the spinning humidity was 50%, and electrospinning was performed in an electrospinning device to obtain primary fibers; the primary fibers were allowed to stand at 58°C for 2.2 h, and dried at 70°C under vacuum conditions for 9 h to obtain polyamide fibers; the polyamide fibers were spun in a spinning machine to obtain acid- and alkali-resistant and anti-aging spinning yarns.
[0034] Embodiment 2:
[0035] A method for preparing an acid- and alkali-resistant anti-aging spun yarn, the method comprising the following preparation steps:
[0036] (1) 4-anilinotriethoxysilane and deionized water were mixed at a mass ratio of 1:19, and the pH was adjusted to 6 with an oxalic acid aqueous solution with a mass fraction of 11%. The mixture was stirred at 250 r / min for 20 min at room temperature to prepare a silane hydrolyzate. Nano-montmorillonite and anhydrous ethanol were mixed at a mass ratio of 1:60, and 6.5 times the mass of the nano-montmorillonite silane hydrolyzate was added. The mixture was stirred at 57° C. and 250 r / min for 1.1 h, and filtered. Wash with anhydrous ethanol 4 times, dry at 57°C for 9 hours under vacuum conditions to obtain pre-modified nano-montmorillonite; mix the pre-modified nano-montmorillonite and toluene in a mass ratio of 1:53, ultrasonically disperse for 25 minutes, add 4-(dimethylamino) salicylaldehyde 3 times the mass of the pre-modified nano-montmorillonite, stir and react at 63°C, 250r / min for 3.5 hours, filter, wash with toluene 4 times, dry at 69°C for 9 hours under vacuum conditions to obtain modified nano-montmorillonite;
[0037] (2) 3-(diethoxymethylsilyl)propylamine and diphenylphosphine were added in a molar ratio of 1:1 to acetonitrile with a mass of 11 times that of 3-(diethoxymethylsilyl)propylamine, and cuprous iodide with a mass of 0.04 times that of 3-(diethoxymethylsilyl)propylamine was added, and the mixture was stirred at 56°C and 250 r / min for 4.5 h, and dried at 70°C under vacuum for 9 h to obtain phosphorus-containing diethoxysilane; 3-chloropropylmethyldiethoxysilane and phosphorus-containing diethoxysilane were added in a molar ratio of 1:1.2 to the reaction mixture. In the reaction kettle, add deionized water of 1.3 times the mass of 3-chloropropylmethyldiethoxysilane and lithium hydroxide of 0.025 times the mass of 3-chloropropylmethyldiethoxysilane, and heat to 81°C at a rate of 3°C / min under stirring at 150r / min, continue stirring and reacting for 30min, wash with a mixture of equal volumes of deionized water and toluene, stand for stratification, remove the aqueous phase, repeat washing 5 times, take the organic phase and place it in a drying oven, dry it at 60°C for 9h under vacuum conditions, and obtain a phosphorus silicon flame retardant additive;
[0038] (3) adding 3,3',4,4'-biphenyltetracarboxylic acid dianhydride and 4,4'-(hexafluoroisopropylene) diphthalic anhydride in a molar ratio of 1:0.5 to N,N-dimethylformamide (7.5 times the mass of 3,3',4,4'-biphenyltetracarboxylic acid dianhydride), and mixing them uniformly to prepare a dianhydride reaction liquid; mixing 3,3',4,4'-biphenyltetracarboxylic acid dianhydride, 1,6-hexanediamine (1 times the total molar amount of 4,4'-(hexafluoroisopropylene) diphthalic anhydride), and N,N-dimethylformamide in a mass ratio of 1:7 uniformly, stirring at 20°C and 250 r / min for 11 minutes under nitrogen protection, adding the dianhydride reaction liquid, stirring at 20°C and 400 r / min for 19 hours under nitrogen atmosphere to prepare a polyamic acid solution; mixing the polyamic acid solution and N 4 ,N 4 -dimethyl-1,2,4-phenyltriamine and a hydrochloric acid aqueous solution with a molar concentration of 4 mol / L were mixed uniformly in a mass ratio of 1:0.23:0.07, stirred at 85°C and 70 r / min for 7.5 h, and dried at 77°C for 10 h under vacuum conditions to obtain a functionalized polyamide;
[0039] (4) Functionalized polyamide, modified nano-montmorillonite, phosphorus silicon flame retardant additive, and N,N-dimethylformamide were mixed uniformly in a mass ratio of 1:0.05:0.07:6.5, and stirred at 20°C and 110 r / min for 19 min to prepare a spinning solution; the spinning solution was loaded into a micro pump, and an aluminum foil covered on an ice plate was used as a receiving device, and the receiving distance was adjusted to 17 cm. During the spinning process, the voltage was 24 kV, the propulsion rate was 0.65 mL / h, the ambient temperature was 25°C, and the spinning humidity was 55%. Electrospinning was performed in an electrospinning device to obtain primary fibers; the primary fibers were allowed to stand at 59°C for 2.1 h, and dried at 71°C under vacuum conditions for 8 h to obtain polyamide fibers; the polyamide fibers were spun in a spinning machine to obtain acid- and alkali-resistant and anti-aging spinning yarns.
[0040] Embodiment 3:
[0041] A method for preparing an acid- and alkali-resistant anti-aging spun yarn, the method comprising the following preparation steps:
[0042] (1) 4-anilinotriethoxysilane and deionized water were mixed at a mass ratio of 1:20, the pH value was adjusted to 6.2 with a 12% oxalic acid aqueous solution, and the mixture was stirred at room temperature for 15 minutes at 300 r / min to prepare a silane hydrolyzate; nano-montmorillonite and anhydrous ethanol were mixed at a mass ratio of 1:63, 7 times the mass of the silane hydrolyzate of the nano-montmorillonite was added, the mixture was stirred at 58°C and 300 r / min for 1 hour, filtered, washed with anhydrous ethanol 5 times, and dried at 58°C for 8 hours under vacuum conditions to obtain pre-modified nano-montmorillonite; pre-modified nano-montmorillonite and toluene were mixed at a mass ratio of 1:54, ultrasonically dispersed for 30 minutes, 3.2 times the mass of 4-(dimethylamino) salicylaldehyde of the pre-modified nano-montmorillonite was added, the mixture was stirred at 66°C and 300 r / min for 3 hours, filtered, washed with toluene 5 times, and dried at 70°C for 8 hours under vacuum conditions to obtain modified nano-montmorillonite;
[0043] (2) 3-(diethoxymethylsilyl)propylamine and diphenylphosphine were added in a molar ratio of 1:1 to acetonitrile with a mass of 12 times that of 3-(diethoxymethylsilyl)propylamine, and cuprous iodide with a mass of 0.05 times that of 3-(diethoxymethylsilyl)propylamine was added, and the mixture was stirred at 57°C and 300 r / min for 4 h, and dried at 71°C under vacuum for 8 h to obtain phosphorus-containing diethoxysilane; 3-chloropropylmethyldiethoxysilane and phosphorus-containing diethoxysilane were added in a molar ratio of 1:1.3 to the reaction mixture. In the reaction kettle, add deionized water of 1.4 times the mass of 3-chloropropylmethyldiethoxysilane and lithium hydroxide of 0.03 times the mass of 3-chloropropylmethyldiethoxysilane, and heat to 82°C at a rate of 3°C / min under stirring at 200r / min, continue stirring and reacting for 28min, wash with a mixture of equal volumes of deionized water and toluene, stand for stratification, remove the water phase, repeat washing 6 times, take the organic phase and place it in a drying oven, dry it at 62°C under vacuum conditions for 8h, and obtain a phosphorus silicon flame retardant additive;
[0044] (3) adding 3,3',4,4'-biphenyltetracarboxylic acid dianhydride and 4,4'-(hexafluoroisopropylene) diphthalic anhydride in a molar ratio of 1:0.6 to N,N-dimethylformamide (8 times the mass of 3,3',4,4'-biphenyltetracarboxylic acid dianhydride), and mixing them evenly to prepare a dianhydride reaction liquid; mixing 3,3',4,4'-biphenyltetracarboxylic acid dianhydride and 1,6-hexanediamine (1 times the total molar amount of 4,4'-(hexafluoroisopropylene) diphthalic anhydride), and N,N-dimethylformamide in a mass ratio of 1:8 evenly, stirring at 30°C and 300 r / min for 10 minutes under nitrogen protection, adding the dianhydride reaction liquid, stirring at 30°C and 500 r / min for 18 hours under nitrogen atmosphere to prepare a polyamic acid solution; mixing the polyamic acid solution and N 4 ,N 4 -Dimethyl-1,2,4-phenyltriamine and a hydrochloric acid aqueous solution with a molar concentration of 4 mol / L were mixed uniformly in a mass ratio of 1:0.24:0.08, stirred at 90°C and 80 r / min for 7 hours, and dried at 78°C under vacuum conditions for 9 hours to obtain a functionalized polyamide;
[0045] (4) Functionalized polyamide, modified nano-montmorillonite, phosphorus silicon flame retardant additive, and N,N-dimethylformamide were mixed uniformly in a mass ratio of 1:0.06:0.08:7, and stirred at 30°C and 120 r / min for 18 min to prepare a spinning solution; the spinning solution was loaded into a micro pump, and an aluminum foil covered on an ice plate was used as a receiving device, and the receiving distance was adjusted to 18 cm. During the spinning process, the voltage was 25 kV, the propulsion rate was 0.7 mL / h, the ambient temperature was 30°C, and the spinning humidity was 60%, and electrospinning was performed in an electrospinning device to obtain nascent fibers; the nascent fibers were allowed to stand at 60°C for 2 h, and dried at 72°C under vacuum conditions for 7 h to obtain polyamide fibers; the polyamide fibers were spun in a spinning machine to obtain acid- and alkali-resistant and anti-aging spinning yarns.
[0046] Comparative Example 1:
[0047] The difference between the preparation method of the acid-resistant, alkali-resistant and aging-resistant spun yarn of Comparative Example 1 and Example 2 is that step (1) is not performed, and step (4) is modified as follows: functionalized polyamide, nano-montmorillonite, phosphorus silicon flame retardant additive, and N,N-dimethylformamide are mixed evenly in a mass ratio of 1:0.05:0.07:6.5, and stirred at 20°C and 110r / min for 19min to prepare a spinning solution; the spinning solution is loaded into a micro pump, and an ice plate covered with aluminum foil is used as a receiving device, and the receiving distance is adjusted to 17cm. During the spinning process, the voltage is 24kV, the propulsion rate is 0.65mL / h, the ambient temperature is 25°C, and the spinning humidity is 55%, and electrostatic spinning is performed in an electrospinning device to obtain primary fibers; the primary fibers are allowed to stand at 59°C for 2.1h, and dried at 71°C for 8h under vacuum conditions to obtain polyamide fibers; the polyamide fibers are spun in a spinning machine to obtain acid-resistant, alkali-resistant and aging-resistant spun yarn. The remaining steps are the same as in Example 2.
[0048] Comparative Example 2:
[0049] The difference between the preparation method of the acid-base resistant and anti-aging spun yarn of Comparative Example 2 and that of Example 2 lies in the difference in step (2). Step (2) is modified as follows: 3-(diethoxymethylsilyl)propylamine and diphenylphosphine are added in a molar ratio of 1:1 to acetonitrile with a mass of 11 times that of 3-(diethoxymethylsilyl)propylamine, and cuprous iodide with a mass of 0.04 times that of 3-(diethoxymethylsilyl)propylamine is added, and the reaction is stirred at 56°C and 250r / min for 4.5h, and dried at 70°C under vacuum for 9h to obtain phosphorus-containing diethoxysilane; dimethyl diethoxy Silane and phosphorus-containing diethoxysilane were added to the reactor in a molar ratio of 1:1.2, and deionized water of 1.3 times the mass of dimethyldiethoxysilane and lithium hydroxide of 0.025 times the mass of dimethyldiethoxysilane were added. The temperature was raised to 81°C at a rate of 3°C / min under stirring at 150r / min, and the stirring reaction was continued for 30min. The mixture was washed with an equal volume of deionized water and toluene, and the mixture was allowed to stand for stratification, the aqueous phase was removed, and the washing was repeated 5 times. The organic phase was placed in a drying oven and dried at 60°C for 9h under vacuum to obtain a phosphorus-silicon flame retardant additive. The remaining steps were the same as in Example 2.
[0050] Comparative Example 3:
[0051] The difference between the preparation method of the acid-base resistant and anti-aging spinning yarn of Comparative Example 3 and Example 2 is that step (2) is not performed, and step (4) is modified as follows: functionalized polyamide, modified nano-montmorillonite, and N,N-dimethylformamide are mixed uniformly in a mass ratio of 1:0.05:6.5, stirred at 20°C and 110r / min for 19min, and prepared into a spinning solution; the spinning solution is loaded into a micro pump, and an aluminum foil is covered on an ice plate as a receiving device, and the receiving distance is adjusted to 17cm. During the spinning process, the voltage is 24kV, the propulsion rate is 0.65mL / h, the ambient temperature is 25°C, and the spinning humidity is 55%, and electrostatic spinning is performed in an electrostatic spinning device to obtain primary fibers; the primary fibers are left to stand at 59°C for 2.1h, and dried at 71°C for 8h under vacuum conditions to obtain polyamide fibers; the polyamide fibers are spun in a spinning machine to obtain acid-base resistant and anti-aging spinning yarns. The remaining steps are the same as in Example 2.
[0052] Comparative Example 4:
[0053] The preparation method of the acid-base resistant and anti-aging spun yarn of Comparative Example 4 is different from that of Example 2 only in step (3). Step (3) is modified as follows: 3,3',4,4'-biphenyltetracarboxylic acid dianhydride and N,N-dimethylformamide are mixed uniformly in a mass ratio of 1.5:7.5 to prepare a dianhydride reaction solution; 1,6-hexanediamine and N,N-dimethylformamide with a molar amount of 1 times that of 3,3',4,4'-biphenyltetracarboxylic acid dianhydride are mixed uniformly in a mass ratio of 1:7, and stirred at 20 ° C and 250 r / min for 11 min under nitrogen protection, and the dianhydride reaction solution is added, and the reaction is stirred at 20 ° C and 400 r / min for 19 h under a nitrogen atmosphere to obtain a polyamic acid solution; the polyamic acid solution and N 4 ,N 4 -dimethyl-1,2,4-phenyltriamine and a hydrochloric acid aqueous solution with a molar concentration of 4 mol / L were mixed uniformly in a mass ratio of 1:0.23:0.07, stirred at 85°C and 70 r / min for 7.5 hours, and dried at 77°C for 10 hours under vacuum conditions to obtain functionalized polyamide. The remaining steps were the same as in Example 2.
[0054] Comparative Example 5:
[0055] The preparation method of the acid-base resistant and anti-aging spun yarn of Comparative Example 5 is different from that of Example 2 only in step (3). Step (3) is modified as follows: 3,3',4,4'-biphenyltetracarboxylic acid dianhydride and 4,4'-(hexafluoroisopropylene) diphthalic anhydride are added in a molar ratio of 1:0.5 to N,N-dimethylformamide (7.5 times the mass of 3,3',4,4'-biphenyltetracarboxylic acid dianhydride), and the mixture is uniformly mixed to prepare a dianhydride reaction solution; 3,3',4 , 4'-biphenyltetracarboxylic dianhydride, 1 times the total molar amount of 4,4'-(hexafluoroisopropylene) diphthalic anhydride, 1,6-hexanediamine, and N,N-dimethylformamide were mixed uniformly in a mass ratio of 1:7, stirred at 20°C, 250r / min for 11min under nitrogen protection, added with dianhydride reaction liquid, stirred at 20°C, 400r / min for 19h under nitrogen atmosphere, and dried at 77°C for 10h under vacuum conditions to obtain functionalized polyamide. The remaining steps are the same as those in Example 2.
[0056] Test Example 1
[0057] Acid and alkali resistance test
[0058] Acid resistance test method: Dry the embodiment and comparative example at 75°C for 6h under vacuum conditions, and weigh the initial mass M of the embodiment and comparative example; immerse the embodiment and comparative example in a hydrochloric acid aqueous solution with a mass fraction of 8%, ultrasonically oscillate at 35°C for 5h, take out, wash with deionized water 4 times, dry at 75°C for 10h under vacuum conditions, weigh the mass N of the embodiment and comparative example after acid treatment, and calculate the mass loss rate of the embodiment and comparative example after acid treatment, acid treatment mass loss rate = (MN) / M×100%. The results are shown in Table 1.
[0059] Alkali resistance test method: dry the embodiment and comparative example at 75°C for 6h under vacuum conditions, and weigh the initial mass X of the embodiment and comparative example; immerse the embodiment and comparative example in an aqueous sodium hydroxide solution with a mass fraction of 8%, ultrasonically oscillate at 35°C for 5h, take out, wash with deionized water 4 times, dry at 75°C for 10h under vacuum conditions, weigh the mass Y of the embodiment and comparative example after alkali treatment, and calculate the mass loss rate of the embodiment and comparative example after alkali treatment, alkali treatment mass loss rate = (XY) / X×100%. The results are shown in Table 1.
[0060] Table 1
[0061]
[0062] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 1, it can be found that the acid-base resistant and anti-aging spun yarn prepared by the present invention has good acid-base resistance.
[0063] By comparison, the acid treatment mass loss rate and alkali treatment mass loss rate of Examples 1 to 3 are both lower than those of Comparative Example 1, indicating that nano-montmorillonite is a two-dimensional inorganic nanomaterial. The surface modification improves the dispersibility of nano-montmorillonite in the resin, so that the nano-montmorillonite is evenly dispersed in the resin to form a physical barrier, making the diffusion process of water molecules more tortuous and slow, reducing the penetration of gases and liquids, and improving the acid and alkali resistance of the acid-resistant and alkali-resistant aging spinning yarn.
[0064] By comparison, the acid treatment mass loss rate and alkali treatment mass loss rate of Examples 1 to 3 are all less than the acid treatment mass loss rate and alkali treatment mass loss rate of Comparative Example 4, indicating that 3,3',4,4'-biphenyltetracarboxylic dianhydride, 4,4'-(hexafluoroisopropylene) diphthalic anhydride and 1,6-hexamethylenediamine are polymerized to prepare a polyamic acid solution; the carboxyl groups on the side chains of the polyamic acid molecules in the polyamic acid solution are reacted with N 4 ,N 4-O-phenylenediamine reacts with dimethyl-1,2,4-phenyltriamine to generate a benzimidazole structure to obtain functionalized polyamide, and at the same time, fluorine atoms are introduced into the side chains of the functionalized polyamide molecules; the electronegativity of the fluorine atoms introduced into the side chains of the functionalized polyamide molecules is very large, which enables the fluorine atoms to strongly attract electrons and form a stable CF bond. Due to the high bond energy of the CF bond and the low surface tension of the fluorocarbon chain, the acid-base resistant and anti-aging spinning yarn has hydrophobicity and oleophobicity, giving the acid-base resistant and anti-aging spinning yarn excellent acid-base resistance.
[0065] Test Example 2
[0066] Testing of mechanical properties and anti-aging properties
[0067] Test method: Referring to GB / T3916-2013, the breaking strength A of the embodiment and the comparative example was tested using a YG061F electronic single yarn strength tester; the embodiment and the comparative example were irradiated with a xenon lamp for 10 days, and the breaking strength B of the embodiment and the comparative example after ultraviolet treatment was tested, and the breaking strength change rate of the embodiment and the comparative example before and after ultraviolet aging treatment was calculated; breaking strength change rate = (AB) / A×100%. The results are shown in Table 2.
[0068] Table 2
[0069]
[0070] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 2, it can be found that the acid-base resistant and anti-aging spun yarn prepared by the present invention has good mechanical properties and anti-aging properties.
[0071] By comparison, the breaking strength of Examples 1 to 3 is greater than that of Comparative Example 1, indicating that pre-modified nano-montmorillonite is obtained by reacting nano-montmorillonite and 4-anilinotriethoxysilane, and aniline is introduced into the pre-modified nano-montmorillonite; the aniline on the pre-modified nano-montmorillonite reacts with the aldehyde group on 4-(dimethylamino) salicylaldehyde to generate a salicylaldehyde aniline Schiff base structure, and a tertiary amine structure is introduced to obtain modified nano-montmorillonite; the tertiary amine structure introduced into the modified nano-montmorillonite can react with the chlorine atom on the phosphosilicate flame retardant additive to generate a quaternary ammonium salt, forming a cross-linked network structure, thereby improving the mechanical properties of the acid, alkali and aging resistant spinning yarn.
[0072] By comparison, the breaking strength of Examples 1 to 3 is greater than that of Comparative Examples 2 to 3, indicating that the phosphorus silicon flame retardant additive is prepared by condensation of 3-chloropropylmethyldiethoxysilane and phosphorus-containing diethoxysilane, and chlorine atoms are introduced into the side chains of the phosphorus silicon flame retardant additive; the chlorine atoms introduced into the side chains of the phosphorus silicon flame retardant additive can react with the tertiary amine structure introduced into the modified nano-montmorillonite and the functionalized polyamide to generate a quaternary ammonium salt structure, forming a cross-linked network, inhibiting the relative slip between molecular chains, and improving the mechanical properties of the acid, alkali and aging resistant spinning yarn.
[0073] By comparison, the breaking strength of Examples 1 to 3 is greater than that of Comparative Example 5, indicating that 3,3',4,4'-biphenyltetracarboxylic anhydride, 4,4'-(hexafluoroisopropylene) diphthalic anhydride and 1,6-hexamethylenediamine are polymerized to prepare a polyamic acid solution; the carboxyl groups on the side chains of the polyamic acid molecules in the polyamic acid solution are reacted with N 4 ,N 4 -O-phenylenediamine reacts with dimethyl-1,2,4-phenyltriamine to generate a benzimidazole structure to obtain a functionalized polyamide, and at the same time, a tertiary amine structure is introduced on the side chain of the functionalized polyamide molecule; the tertiary amine structure introduced on the side chain of the functionalized polyamide molecule can react with the chlorine atom introduced on the side chain of the phosphorus silicon flame retardant additive to generate a quaternary ammonium salt structure, forming a cross-linked network, inhibiting the relative slip between the molecular chains, and improving the mechanical properties of the acid, alkali and aging resistant spinning yarn.
[0074] By comparison, the breaking strength change rate of Examples 1 to 3 is less than that of Comparative Example 1, indicating that pre-modified nano-montmorillonite is prepared by reacting nano-montmorillonite and 4-anilinotriethoxysilane, and aniline is introduced into the pre-modified nano-montmorillonite; the aniline on the pre-modified nano-montmorillonite reacts with the aldehyde group on 4-(dimethylamino) salicylaldehyde to generate a salicylaldehyde aniline Schiff base structure to obtain modified nano-montmorillonite; there is a hydroxyl group at the ortho position of the C=N double bond in the salicylaldehyde aniline Schiff base structure, and under ultraviolet light irradiation, the hydrogen atom on the hydroxyl group in the molecular structure will transfer from the oxygen atom to the ortho position of the nitrogen atom, and intramolecular proton transfer will occur, and the configuration of the salicylaldehyde aniline Schiff base structure will be converted from the enol form to the keto form, and the generated keto form is unstable, and is converted into the enol form under light or heating, thereby dissipating the ultraviolet light absorption, giving the acid-base resistant and anti-aging spinning line excellent anti-aging properties.
[0075] Test Example 3
[0076] Antimicrobial performance testing
[0077] Test method: The antibacterial performance of the embodiment and the comparative example was analyzed by comparing the number of E. coli colonies cultured in agar medium for 16 hours using the oscillation method GB / T20944.3. The results are shown in Table 3.
[0078] Table 3
[0079] Antibacterial rate (%) Antibacterial rate (%) Example 1 99.87 Comparative Example 1 95.37 Example 2 99.96 Comparative Example 2 90.18 Example 3 99.94 Comparative Example 3 89.22 Comparative Example 4 99.86 Comparative Example 5 85.61
[0080] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 3, it can be found that the acid-base resistant and anti-aging spun yarn prepared by the present invention has good antibacterial properties.
[0081] By comparison, the antibacterial rates of Examples 1 to 3 are greater than that of Comparative Example 1, indicating that pre-modified nano-montmorillonite is prepared by reacting nano-montmorillonite and 4-anilinotriethoxysilane, and aniline is introduced into the pre-modified nano-montmorillonite; the aniline on the pre-modified nano-montmorillonite is reacted with the aldehyde group on 4-(dimethylamino) salicylaldehyde to generate a salicylaldehyde aniline Schiff base structure, and a tertiary amine structure is introduced to obtain modified nano-montmorillonite; the tertiary amine structure introduced into the modified nano-montmorillonite can react with the chlorine atom on the phosphosilicate flame retardant additive to generate a quaternary ammonium salt, and the generated quaternary ammonium salt structure can improve the antibacterial properties of the acid-, alkali-, and aging-resistant spinning yarn.
[0082] By comparison, the antibacterial rates of Examples 1 to 3 are greater than those of Comparative Examples 2 to 3, indicating that the phosphosilicate flame retardant additive is prepared by condensation of 3-chloropropylmethyldiethoxysilane and phosphorus-containing diethoxysilane, and chlorine atoms are introduced into the side chains of the phosphosilicate flame retardant additive; the chlorine atoms introduced into the side chains of the phosphosilicate flame retardant additive can react with the tertiary amine structure introduced into the modified nano-montmorillonite and the functionalized polyamide to generate a quaternary ammonium salt structure, and the generated quaternary ammonium salt structure can improve the antibacterial properties of the acid-, alkali-resistant and aging-resistant spinning yarn.
[0083] By comparison, the antibacterial rates of Examples 1 to 3 are greater than those of Comparative Example 5, indicating that 3,3',4,4'-biphenyltetracarboxylic anhydride, 4,4'-(hexafluoroisopropylene) diphthalic anhydride and 1,6-hexamethylenediamine are polymerized to prepare a polyamic acid solution; the carboxyl groups on the side chains of the polyamic acid molecules in the polyamic acid solution are reacted with N 4 ,N 4 -O-phenylenediamine reacts with dimethyl-1,2,4-phenyltriamine to generate a benzimidazole structure to obtain a functionalized polyamide, and at the same time, a tertiary amine structure is introduced into the side chain of the functionalized polyamide molecule; the generated benzimidazole structure can improve the antibacterial properties of the acid-resistant, alkali-resistant, and anti-aging spinning yarn; the tertiary amine structure introduced into the side chain of the functionalized polyamide molecule can react with the chlorine atom introduced into the side chain of the phosphorus silicon flame retardant additive to generate a quaternary ammonium salt structure, and the generated quaternary ammonium salt structure has excellent antibacterial properties and can improve the antibacterial properties of the acid-resistant, alkali-resistant, and anti-aging spinning yarn.
[0084] Test Example 4
[0085] Flame retardant performance test
[0086] Test method: According to GB / T5454 "Textile Combustion Performance Test Oxygen Index Method", the limiting oxygen index of the examples and comparative examples was tested using an oxygen index instrument. The results are shown in Table 4.
[0087] Table 4
[0088] Limiting oxygen index (%) Limiting oxygen index (%) Example 1 30.68 Comparative Example 1 30.88 Example 2 31.21 Comparative Example 2 30.32 Example 3 30.95 Comparative Example 3 23.13 Comparative Example 4 30.27 Comparative Example 5 30.08
[0089] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 4, it can be found that the acid-base resistant and aging-resistant spun yarn prepared by the present invention has good flame retardant properties.
[0090] By comparison, the limiting oxygen index of Examples 1 to 3 is greater than that of Comparative Example 3, indicating that the amino group on 3-(diethoxymethylsilyl)propylamine reacts with the PH bond on diphenylphosphine to obtain phosphorus-containing diethoxysilane; 3-chloropropylmethyldiethoxysilane and phosphorus-containing diethoxysilane are polycondensed to obtain the phosphorus silicon flame retardant additive, Si-O-Si bonds are generated on the main chain of the phosphorus silicon flame retardant additive, and phosphorus elements are introduced on the side chains; the bond energy of the Si-O bond is greater than that of the CC bond, and a dense barrier carbon layer is formed during the combustion process. This carbon layer can effectively prevent heat conduction and oxygen diffusion, thereby improving the flame retardant properties of the acid, alkali and aging-resistant spinning yarn, and the introduction of phosphorus elements further improves the flame retardancy.
[0091] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A kind of acid and alkali resistant and anti-aging spinning yarn, characterized in that: The acid-base resistant and anti-aging spinning yarn is prepared by reacting pre-modified nano-montmorillonite and 4-(dimethylamino) salicylaldehyde to obtain modified nano-montmorillonite; polycondensing 3-chloropropylmethyldiethoxysilane and phosphorus-containing diethoxysilane to obtain phosphorus silicon flame retardant additive; 4 ,N 4 -dimethyl-1,2,4-phenyltriamine is reacted to obtain functionalized polyamide; functionalized polyamide, modified nano-montmorillonite and phosphorus silicon flame retardant additive are prepared into spinning solution, and polyamide fiber is obtained by electrostatic spinning; polyamide fiber is spun in a spinning machine to obtain acid-base resistant and anti-aging spinning yarn; The pre-modified nano-montmorillonite is prepared by reacting nano-montmorillonite and 4-anilinotriethoxysilane; The phosphorus-containing diethoxysilane is prepared by reacting 3-(diethoxymethylsilyl)propylamine and diphenylphosphine; The polyamic acid solution is prepared by polymerizing 3,3',4,4'-biphenyltetracarboxylic dianhydride, 4,4'-(hexafluoroisopropylene) diphthalic anhydride and 1,6-hexamethylenediamine.
2. A method for preparing acid-base resistant and anti-aging spinning yarn, characterized in that: The method for preparing the acid-base resistant and anti-aging spun yarn comprises the following preparation steps: (1) Pre-modified nano-montmorillonite and toluene are mixed uniformly in a mass ratio of 1:(52-54), ultrasonically dispersed for 20-30 min, 4-(dimethylamino) salicylaldehyde in an amount of 2.8-3.2 times the mass of the pre-modified nano-montmorillonite is added, stirred at 60-66°C and 200-300 r / min for 3-4 h, filtered, washed with toluene 3-5 times, and dried at 68-70°C under vacuum conditions for 8-10 h to obtain modified nano-montmorillonite; (2) 3-chloropropylmethyldiethoxysilane and phosphorus-containing diethoxysilane are added to a reaction kettle in a molar ratio of 1:(1.1-1.3), deionized water of 1.2-1.4 times the mass of 3-chloropropylmethyldiethoxysilane and lithium hydroxide of 0.02-0.03 times the mass of 3-chloropropylmethyldiethoxysilane are added, and the temperature is raised to 80-82°C at a rate of 3°C / min under stirring conditions of 100-200 r / min, and the stirring reaction is continued for 28-32 minutes, and the mixture is washed with an equal volume of deionized water and toluene, and the mixture is allowed to stand for stratification, and the aqueous phase is removed, and the washing is repeated 4-6 times, and the organic phase is placed in a drying oven, and dried at 58-62°C for 8-10 hours under vacuum conditions to obtain a phosphorus silicon flame retardant additive; (3) adding 3,3',4,4'-biphenyltetracarboxylic acid dianhydride and 4,4'-(hexafluoroisopropylene) diphthalic anhydride in a molar ratio of 1:(0.4-0.6) to N,N-dimethylformamide which is 7-8 times the mass of 3,3',4,4'-biphenyltetracarboxylic acid dianhydride, and mixing them uniformly to prepare a dianhydride reaction liquid; adding 3,3',4,4'-biphenyltetracarboxylic acid dianhydride, 4,4'-(hexafluoroisopropylene) diphthalic anhydride, and the mixture is stirred for 2 h. 1 times the molar amount of 1,6-hexanediamine and N,N-dimethylformamide are mixed uniformly in a mass ratio of 1:(6-8), stirred at 10-30°C and 200-300r / min for 10-12min under nitrogen protection, and the dianhydride reaction liquid is added, and stirred at 10-30°C and 300-500r / min for 18-20h under nitrogen atmosphere to obtain a polyamic acid solution; the polyamic acid solution and N 4 ,N 4 -Dimethyl-1,2,4-phenyltriamine and hydrochloric acid aqueous solution are mixed uniformly in a mass ratio of 1:(0.22-0.24):(0.06-0.08), stirred at 80-90°C and 60-80r / min for 7-8h, and dried at 76-78°C under vacuum conditions for 9-11h to obtain functionalized polyamide; (4) Functionalized polyamide, modified nano-montmorillonite, phosphorus silicon flame retardant additive and N,N-dimethylformamide are mixed uniformly, and stirred at 10-30°C and 100-120 r / min for 18-20 min to prepare a spinning solution; the spinning solution is loaded into a micro pump, and an ice plate covered with aluminum foil is used as a receiving device, and electrospinning is performed in an electrospinning device to obtain spun fibers; the spun fibers are allowed to stand at 58-60°C for 2-2.2 h, and dried at 70-72°C under vacuum conditions for 7-9 h to obtain polyamide fibers; the polyamide fibers are spun in a spinning machine to obtain acid- and alkali-resistant and anti-aging spinning yarns.
3. The method for preparing an acid-base resistant and aging-resistant spinning yarn according to claim 2, characterized in that: The preparation method of the pre-modified nano-montmorillonite in step (1) is as follows: nano-montmorillonite and anhydrous ethanol are mixed uniformly in a mass ratio of 1:(57-63), silane hydrolyzate is added in an amount of 6-7 times the mass of the nano-montmorillonite, the mixture is stirred at 56-58°C and 200-300 r / min for 1-1.2 h, filtered, washed with anhydrous ethanol for 3-5 times, and dried at 56-58°C under vacuum conditions for 8-10 h to obtain the pre-modified nano-montmorillonite.
4. The method for preparing an acid- and alkali-resistant and anti-aging spinning yarn according to claim 3, characterized in that: The preparation method of the silane hydrolyzate is as follows: 4-anilinotriethoxysilane and deionized water are uniformly mixed in a mass ratio of 1:(18-20), the pH value is adjusted to 5.8-6.2 with an oxalic acid aqueous solution, and the silane hydrolyzate is prepared by stirring at 200-300 r / min for 15-25 min at room temperature.
5. The method for preparing an acid- and alkali-resistant and anti-aging spinning yarn according to claim 4, characterized in that: The mass fraction of the oxalic acid aqueous solution is 10% to 12%.
6. The method for preparing an acid- and alkali-resistant and anti-aging spinning yarn according to claim 2, characterized in that: The preparation method of the phosphorus-containing diethoxysilane in step (2) is as follows: 3-(diethoxymethylsilyl)propylamine and diphenylphosphine are added in a molar ratio of 1:1 to acetonitrile with a mass of 10 to 12 times that of 3-(diethoxymethylsilyl)propylamine, and cuprous iodide with a mass of 0.03 to 0.05 times that of 3-(diethoxymethylsilyl)propylamine is added, and the mixture is stirred at 55 to 57° C. and 200 to 300 r / min for 4 to 5 hours, and dried at 69 to 71° C. under vacuum conditions for 8 to 10 hours to obtain the phosphorus-containing diethoxysilane.
7. The method for preparing acid-base resistant and aging-resistant spinning yarn according to claim 2, characterized in that: The molar concentration of the hydrochloric acid aqueous solution in step (3) is 4 mol / L.
8. The method for preparing acid-base resistant and aging-resistant spinning yarn according to claim 2, characterized in that: The mass ratio of the functionalized polyamide, modified nano-montmorillonite, phosphorus silicon flame retardant additive and N,N-dimethylformamide in step (4) is 1:(0.04-0.06):(0.06-0.08):(6-7).
9. The method for preparing acid-base resistant and aging-resistant spinning yarn according to claim 2, characterized in that: The process parameters of the electrospinning in step (4) are as follows: adjusting the receiving distance to 16-18 cm, the voltage during spinning to 23-25 kV, the propulsion rate to 0.6-0.7 mL / h, the ambient temperature to 20-30° C., and the spinning humidity to 50%-60%.
Citation Information
Patent Citations
Anti-static fabric and preparation method thereof
CN118390187A
Antibacterial moisture-absorbing fabric containing modified polyester fibers as well as preparation method and application of antibacterial moisture-absorbing fabric
CN118880619A
Preparation method of antibacterial fiber and fabric
CN119177502A